Perceptions and practices of community pharmacists towards antimicrobial stewardship program in Erbil City, Iraq: A cross-sectional study : community pharmacists towards antimicrobial stewardship program - Omar Yassen, Ali; Diyar Bilal , Aya; Saleh Ismael , Bnar; Habeeb Hattab Al-Ani , Ahmad (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Antimicrobial resistance is a crucial health concern around the world, giving rise to millions of deaths each year. Despite the existence of recommendations for antimicrobial stewardship programs (ASP), the problem persists, particularly in conflict-affected areas such as the Middle East. The aim of this study is to investigate pharmacists’ attitude and practices towards ASP in Erbil, Iraq. Methods: A cross-sectional observational study was conducted among community pharmacies in Erbil City, Iraq, from March 2023 to May 2023. 170 Pharmacists completed an electronic questionnaire consisting of three sections: sociodemographic information, perception of ASP, and practices related to ASP. Statistical analysis was performed by using statistical package SPSS version 22 for the social science data. Results: The questionnaire was completed by 170 participants in total, 85 of whom were female and 85 of whom were male. The majority of participants 65.9% were between the ages of 20 and 30, and 71.2% had bachelor’s degrees in pharmacy. The survey indicated 28.2% strongly agreed that “AMS programs improve patient care.” Furthermore, 33.5% strongly agreed that “AMS programs help reduce antimicrobial resistance,” and 31.2% said they frequently administer antibiotics based on complete clinical information. While 24.7% occasionally administered antibiotics in accordance with local guidelines, 33.5% occasionally dispensed antibiotics without a prescription. Notably, 47.6% of those surveyed claimed they would never dispense antibiotics for periods longer than prescribed, even upon patient request. Conclusion: The study shows that community pharmacists in Erbil have favorable views and are responding appropriately to promote antimicrobial stewardship. However, there is room for improvement, especially when it comes to promoting inter-professional collaboration, incorporating AMS programs into community pharmacies, and addressing the issue of providing antibiotics without a valid prescription. These results highlight the necessity of continued measures for patient awareness, education, and training in order to improve the prudent use of antibiotics and guarantee patient safety.